UNLOCKING THE COLOURS WITHIN A CHILD’S EDUCATIONAL GUIDE TO ABSTRACT ART - Velayutham, Vivek; K, Raman (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the potential of abstract art as a tool for nurturing creativity and fostering artistic understanding in children. Drawing upon existing research and educational practices, it proposes a multi-faceted approach to introducing and engaging children with abstract art, ultimately advocating for its role in enriching childhood development. Children’s vibrant imaginations flourish in the boundless realm of abstract art. This guide proposes a multi-sensory approach to unlock their creativity and artistic understanding. Through playful exploration, open-ended questioning, and encounters with diverse materials and artists, children discover the power of colour, shape, and emotion in abstract expression. This journey nurtures their artistic skillset and cultivates critical thinking, self-confidence, and a deeper connection to the world around them. Unlocking the colours within empowers children to become artists and well-rounded individuals equipped to embrace the beauty and possibilities of a creative life.